The potential benefits of using higher X-ray energies for macromolecular crystallography - Garman, E; Dickerson, J (International Union of Crystallography, 2019)
Using X-ray energies higher than those normally used (5–15 keV) for macromolecular X-ray crystallography (MX) at synchrotron sources can theoretically increase the achievable signal as a function of dose and reduce the rate of radiation damage. In practice, a major stumbling block to the use of higher X-ray energy has been the reduced quantum efficiency of silicon detectors as the X-ray energy increases, but hybrid photon-counting CdTe detectors are optimized for higher X-ray energies, and their performance has been steadily improving. Here the potential advantages of using higher incident beam energy together with a CdTe detector for MX are explored, with a particular focus on the advantages that higher beam energies may have for MX experiments with microbeams or microcrystals. Monte Carlo simulations are presented here which for the first time include the efficiency responses of some available X-ray detectors, as well as the possible escape of photoelectrons from the sample and their entry from surrounding material. The results reveal a ‘sweet spot’ at an incident X-ray energy of 26 keV, and show a greater than factor of two improvement in diffraction efficiency at this energy when using microbeams and microcrystals of 5 mm or less.